Radical Spenser Pastoral, Politics and the New Aestheticism - Chamberlain, Richard (Edinburgh University Press, 2022)
GBS_insertPreviewButtonPopup('ISBN:9780748621927);This book provides a radical reading of Edmund Spenser and argues for a re-orientation in Renaissance criticism. It begins by critiquing the new historicist hegemony in Spenser studies, and, through a series of detailed readings, proposes alternative strategies for interpreting the texts of this pivotal Renaissance author which include a politicised 'new aestheticism', eco-criticism, and pastoral theory. Unlike most non-new historicist studies, Radical Spenser argues that Spenser's texts demand a reading at once political and sensitive to aesthetic surprise.Following a polemical Introduction which establishes Spenser's centrality to key problems in contemporary Renaissance studies, Richard Chamberlain shows that William Empson's ideas about pastoral are vital for an understanding of Spenser and early modern literature. The following chapters discuss Spenser's use, in The Shepheardes Calender, of a distinctively 'pastoral' logic to problematise the relationship between literature and criticism; the ways in which this method informs The Faerie Queene; the approach, in the central books of the epic, to textual and state authority; and the final books' exploration of political experience. Finally, by demonstrating the complexity of the critically neglected prose treatise A View of the State of Ireland, the book offers an eco-critical perspective on Spenser's place in the natural and cultural environments of sixteenth-century Ireland.Key FeaturesTheoretical intervention encouraging debate and analysis in Renaissance studies.Close analysis of key passages offers a new understanding of how Spenser's writing works.Broad coverage including readings of Spenser's major poems and his prose dialogue on Ireland.